Use of Combination Antihypertensive Therapy Initiation in Older Americans without Prevalent Cardiovascular Disease. Issue 9 (12th August 2014) - Li, Xiaojuan; Camelo Castillo, Wendy; Stürmer, Til; Pate, Virginia; Gray, Christine L.; Simpson, Ross J.; Setoguchi, Soko; Hanson, Laura C.; Jonsson Funk, Michele
<x xml:space="preserve">Abstract</x> Objectives To describe new users of antihypertensive medications and identify predictors of combination therapy initiation in older Americans. Design Retrospective observational cohort study. Setting Population‐based study using U.S. Medicare fee‐for‐service healthcare claims (2007–2010). Participants Medicare beneficiaries aged 65 and older with no recent diagnoses, procedures, or medications for cardiovascular disease who newly initiated an antihypertensive therapy (n = 275, 493; 210, 605 initiated monotherapy, 64, 888 initiated combination therapy). Measurements Multivariable Poisson regression was used to assess factors associated with initiation of combination therapy versus monotherapy, including participant characteristics, prescriber characteristics, and participant encounters with the healthcare system. Results Initiation of combination therapy increased from 21.9% in 2007 to 24.7% in 2010. The most frequently initiated combinations were angiotensin‐converting enzyme inhibitors with thiazide (29.7%) and angiotensin II receptor antagonists with thiazide (18.7%). Blacks (prevalence ratio (PR) = 1.48, 95% confidence interval (CI) = 1.45–1.51 vs whites), individuals seeing a generalist (PR = 1.10, 95% CI = 1.07–1.14), individuals seeing more than one doctor (PR = 3.38, 95% CI = 3.33–3.44), and participants with no pharmacy claims in the previous 6 months (PR = 1.34, 95% CI = 1.30–1.37 vs ≥3 unique drug classes) were more likely to initiate combination therapy, whereas those who had more outpatient visits in the previous 12 months were less likely to initiate combination therapy (per five visits, PR = 0.82, 95% CI = 0.80–0.83). Conclusion Nearly one in four new users of antihypertensive medications aged 65 and older started treatment with combination therapy. Blacks, individuals living in the south, and those with fewer outpatient physician office visits were more likely to initiate combination therapy. Further research is needed to determine whether this approach to managing hypertension is being well targeted to individuals who will require combination treatment.